Sentiment analysis in Twitter. (January 2014) - MARTÍNEZ-CÁMARA, EUGENIO; MARTÍN-VALDIVIA, M. TERESA; UREÑA-LÓPEZ, L. ALFONSO; MONTEJO-RÁEZ, A RTURO
Abstract In recent years, the interest among the research community in sentiment analysis (SA) has grown exponentially. It is only necessary to see the number of scientific publications and forums or related conferences to understand that this is a field with great prospects for the future. On the other hand, the Twitter boom has boosted investigation in this area due fundamentally to its potential applications in areas such as business or government intelligence, recommender systems, graphical interfaces and virtual assistance. However, to fully understand this issue, a profound revision of the state of the art is first necessary. It is for this reason that this paper aims to represent a starting point for those investigations concerned with the latest references to Twitter in SA.